2013
DOI: 10.1186/1471-2458-13-870
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic variation in the burden of chronic conditions and health care provision – analyzing administrative individual level data from the Basque Country, Spain

Abstract: BackgroundChronic diseases are posing an increasing challenge to society, with the associated burden falling disproportionally on more deprived individuals and geographical areas. Although the existence of a socioeconomic health gradient is one of the main concerns of health policy across the world, health information systems commonly do not have reliable data to detect and monitor health inequalities and inequities. The objectives of this study were to measure the level of socioeconomic-related inequality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 44 publications
4
34
0
Order By: Relevance
“…In most cases, criteria were based on considering that a person has a chronic disease because they have been assigned the corresponding diagnosis (for example, hypertension); for some illnesses other criteria were applied: diagnosis or prescription of specific medications (e.g., for hypothyroidism and Parkinson’s); repeated diagnosis over several years (low back pain); any history of the diagnosis together with prescription of specific drugs in the previous year (asthma and epilepsy); diagnosis the previous year or repeated prescriptions over several months (depression and anxiety); or repeated prescriptions to treat the given health problem (treated dyspepsia). Further information of this methodology can be found in previous publications [ 25 ]. From such 52 health problems list, diabetes mellitus was excluded, and such group was split in two parts: 1) Related chronic comorbidities, that , according to the bibliography [ 8 ], included 7 pathologies: ischaemic heart disease, renal failure, stroke, heart failure, peripheral neuropathy, foot ulcers and diabetic retinopathy; and 2) unrelated chronic diseases, that corresponds to the remaining 44 health problems of the list.…”
Section: Methodsmentioning
confidence: 99%
“…In most cases, criteria were based on considering that a person has a chronic disease because they have been assigned the corresponding diagnosis (for example, hypertension); for some illnesses other criteria were applied: diagnosis or prescription of specific medications (e.g., for hypothyroidism and Parkinson’s); repeated diagnosis over several years (low back pain); any history of the diagnosis together with prescription of specific drugs in the previous year (asthma and epilepsy); diagnosis the previous year or repeated prescriptions over several months (depression and anxiety); or repeated prescriptions to treat the given health problem (treated dyspepsia). Further information of this methodology can be found in previous publications [ 25 ]. From such 52 health problems list, diabetes mellitus was excluded, and such group was split in two parts: 1) Related chronic comorbidities, that , according to the bibliography [ 8 ], included 7 pathologies: ischaemic heart disease, renal failure, stroke, heart failure, peripheral neuropathy, foot ulcers and diabetic retinopathy; and 2) unrelated chronic diseases, that corresponds to the remaining 44 health problems of the list.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies by this research group have revealed high levels (91%) of coexisting disease among women with osteoporosis over 65 years old [ 15 ]. Furthermore, osteoporosis and bronchiectasis are the only two diseases, out of a list of 52, disproportionally more prevalent among women living in richer areas in the Basque Country [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Health systems are always faced with key challenges in relation to primary healthcare. These include developing and retaining workforce, information management, financing the health sector and fair provision[1], distribution of infrastructure and resource allocation management [2,3],affordability, availability and accessibility of health services [4][5][6], and matching services to the needs of the public [7,8]. Based on researches access to health services is a multi factorial issue and dependent on many differ determinate factors including: presence of facilities, personnel population density, socio-economic status, payments required, transport, willingness of health services to accept cultural minorities, physical accessibility for people with disabilities, gender considerations, and cultural attitudes and beliefs about health services and their usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, higher access and use of health services is more needed for some at risk groups such as: mothers, babies, older people or others in the population whose health is relatively more at risk-for example those with chronic health conditions [9][10][11][12][13][14]. In a situation where the provision of services is traditionally measured by indexes such as the number of physicians and hospital beds per unit of population [15], the fair distribution of health services has always been one of the major concerns of health systems worldwide [8,16]. Not to mention, despite the growing rate of economic growth and dramatic advances in the health sector in the last century, there are still huge inequalities in this respect [17][18][19],and this has even been one of the main challenges in developed countries [20], especially in Iran [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation